2008
DOI: 10.1145/1350802.1350811
|View full text |Cite
|
Sign up to set email alerts
|

Complexity metrics for component-oriented software systems

Abstract: Component-based software development (CBSD) has become one of the preferred streams for developing large and complex systems by integrating prefabricated software components that not only facilitates the process of software development but is also changing the ways for software professionals to develop software applications. Till today, numerous attempts have been made by several organizations, software development teams, developers as well as researchers to improve component-oriented software systems (COSS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Many other research for software metrics had been proposed [82]- [89] however for this technique we use CBS metrics that is define in [34]. Their set of metrics requires the CBS system be presented in a graph connectivity.…”
Section: Literature Surveymentioning
confidence: 99%
“…Many other research for software metrics had been proposed [82]- [89] however for this technique we use CBS metrics that is define in [34]. Their set of metrics requires the CBS system be presented in a graph connectivity.…”
Section: Literature Surveymentioning
confidence: 99%
“…Thus, dependency metrics could have a real impact on the quality of the system delivered to the user. Many researchers [3,4,8,9,16,17] focuses on measuring the interaction complexity of integrated components. In the past, only a few papers based on graph theory addressed the evaluation of CBSS dependency [1-3, 5, 10, 14].…”
Section: Figure 1: a Functional Dependency Relationshipmentioning
confidence: 99%
“…Based on above metrics, the authors deduced results as shown in Table1. [16] adopted a similar approach. Authors proposed several interaction metrics for componentbased systems to finally measure the complexity of the system.…”
Section: Dependency Representation Techniquesmentioning
confidence: 99%